Search engine visibility - Thurow, Shari (Voices that matter., 2007)
"Search Engine Visibility is for Web designers and developers, search engine optimizers, usability professionals, and marketers who are seeking to create more effective Web sites that meet both user and business goals. Besides outlining ways to obtain top positions in search results, this book shows you how to design, write, and create user-friendly Web sites. This new edition of Search Engine Visibility includes coverage of blogs, podcasts (both video and audio), Web applications, and more. It also shows you pitfalls to avoid."--Jacket.